Pemphigus vegetans of hallopeau - Nanda Soni; Grover Chander; Garg Vijay; Reddy B (Wolters Kluwer Medknow Publications, 2005)
A 42 year old male had pemphigus vegetans of Hallopeau of groin and perianal area for the last 4 months. He also had lesions on scalp and mouth. Histology showed intraepidermal eosinophilic abscess.